Human vitreous in proliferative diabetic retinopathy: Characterization and translational implications. (September 2019) - Nawaz, Imtiaz M.; Rezzola, Sara; Cancarini, Anna; Russo, Andrea; Costagliola, Ciro; Semeraro, Francesco; Presta, Marco
Abstract: Diabetic retinopathy (DR) is one of the leading causes of visual impairment in the working-age population. DR is a progressive eye disease caused by long-term accumulation of hyperglycaemia-mediated pathological alterations in the retina of diabetic patients. DR begins with asymptomatic retinal abnormalities and may progress to advanced-stage proliferative diabetic retinopathy (PDR), characterized by neovascularization or preretinal/vitreous haemorrhages. The vitreous, a transparent gel that fills the posterior cavity of the eye, plays a vital role in maintaining ocular function. Structural and molecular alterations of the vitreous, observed during DR progression, are consequences of metabolic and functional modifications of the retinal tissue. Thus, vitreal alterations reflect the pathological events occurring at the vitreoretinal interface. These events are caused by hypoxic, oxidative, inflammatory, neurodegenerative, and leukostatic conditions that occur during diabetes. Conversely, PDR vitreous can exert pathological effects on the diabetic retina, resulting in activation of a vicious cycle that contributes to disease progression. In this review, we recapitulate the major pathological features of DR/PDR, and focus on the structural and molecular changes that characterize the vitreal structure and composition during DR and progression to PDR. In PDR, vitreous represents a reservoir of pathological signalling molecules. Therefore, in this review we discuss how studying the biological activity of the vitreous in different in vitro, ex vivo, and in vivo experimental models can provide insights into the pathogenesis of PDR. In addition, the vitreous from PDR patients can represent a novel tool to obtain preclinical experimental evidences for the development and characterization of new therapeutic drug candidates for PDR therapy. Highlights: PDR is the major cause of vision loss in the working age population. Structural and molecular vitreal alterations play a key role in PDR progression. PDR vitreous represents a "reservoir" of pathological signalling molecules. The study of the biological activity of PDR vitreous offers new pathogenic insights. PDR vitreous can be used as a tool for the identification of novel drug candidates.